Increased Serum Levels of Asymmetric Dimethylarginine and Symmetric Dimethylarginine and Decreased Levels of Arginine in Sudanese Patients with Essential Hypertension - Sahar Gamil; Jeanette Erdmann; Edzard Schwedhelm; Khalid Hussein Bakheit; Ihab B.B. Abdalrahman; Abdelrahim O. Mohamed (Karger Publishers, 2020)
Introduction: Essential hypertension (EH) is a disease caused by various environmental and genetic factors. Nitric oxide (NO) is important for the functional integrity of the endothelium. It is produced in endothelial cells by endothelial NO synthase (eNOS) that mediates the conversion of the amino acid arginine into NO and citrulline. Asymmetric dimethylarginine (ADMA) acts as an inhibitor of eNOS. In contrast, symmetric dimethylarginine (SDMA) has no direct effect on eNOS but plays an important role competing with arginine for transport across the amino acid transporter. ADMA and SDMA have been found to play a central role in the development of cardiovascular diseases. Serum ADMA levels may serve as a future diagnostic marker and a target of therapy in hypertensive patients in the Sudanese population. This study aimed to investigate the relation between serum arginine, ADMA, and SDMA levels with EH in the Sudanese population. Methods: Patients (n = 260) with established hypertension and controls (n = 144) with normal blood pressure were included in this case-control study. Serum blood samples were analyzed for arginine, ADMA, and SDMA, using high-performance liquid chromatography-tandem mass spectrometry. Other laboratory data were measured using routine methods. Mann-Whitney's U test and χ2 tests were used for continuous and categorical data, respectively. A multivariate logistic regression analysis was conducted to investigate the independent effect of multiple variables on the development of hypertension. Results: Serum arginine levels were significantly lower in the patient group than in the control group (p < 0.001). ADMA and SDMA levels were significantly higher in the patient group than the control group (p < 0.001, p = 0.001, respectively). Multivariate logistic regression analysis showed that only older age, being a male, and arginine levels are independent factors controlling the development of hypertension (p < 0.001, p < 0.001, and p = 0.046, respectively). ADMA and SDMA levels were not independent factors for the development of hypertension. Conclusions: This study demonstrated increased serum levels of ADMA and SDMA and decreased arginine levels in Sudanese patients with EH. Lowering serum ADMA levels or increasing the arginine levels might be a novel therapeutic target in these individuals.